2010
DOI: 10.1007/s12022-010-9126-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher Frequency of Thyroid Tumors in the Right Lobe

Abstract: Recently, using ultrasonography, we observed that the right lobe usually is larger compared with the left thyroid lobe. Since the higher cell number in a larger right lobe may confer a higher tumor risk, we investigated the location of benign and malignant lesions to test the hypothesis of a more frequent occurrence in this lobe. In 1,001 consecutive patients with benign thyroid lesions, tumors more frequently occurred in the right lobe (+21.5%, p = 0.0022). Furthermore, in 1,277 thyroid cancer patients with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…In 41.8 percent of cases, malignant nodules were found in the right lobe, 40.8 percent in the left lobe, 5.8 percent in the bilateral lobe, and 3.9 percent in the isthmus, 2.9 percent in right Loboisthmic, while in 4.8 percent surgical specimen was not oriented. Several studies have indicated that the right lobe contains an increased number of cells that may contribute to a greater risk of tumor development (Gessl et al, 2010). Our findings were in contrast to that of (Bendouida et al, 2016), in which the majority of patients had malignant nodules located in the left lobe.…”
Section: Discussioncontrasting
confidence: 92%
“…In 41.8 percent of cases, malignant nodules were found in the right lobe, 40.8 percent in the left lobe, 5.8 percent in the bilateral lobe, and 3.9 percent in the isthmus, 2.9 percent in right Loboisthmic, while in 4.8 percent surgical specimen was not oriented. Several studies have indicated that the right lobe contains an increased number of cells that may contribute to a greater risk of tumor development (Gessl et al, 2010). Our findings were in contrast to that of (Bendouida et al, 2016), in which the majority of patients had malignant nodules located in the left lobe.…”
Section: Discussioncontrasting
confidence: 92%
“…Renal cell carcinoma (RCC) located on the left with tumor thrombus does not have a worse prognosis than RCC located on the right [3]. In the thyroid, Gessl et al showed that a larger proportion of both benign and malignant tumors tended to affect the right lobe [4]. However, no study has attempted to investigate differences in features between the right and left hepatic lobes.…”
Section: Introductionmentioning
confidence: 99%